Reversible Computation 8th International Conference, RC 2016, Bologna, Italy, July 7-8, 2016, Proceedings - Devitt, Simon; Lanese, Ivan (Programming and Software Engineering, 2016)
This book constitutes the refereed proceedings of the 8th International Conference on Reversible Computation, RC 2016, held in Bologna, Italy, in July 2016. The 18 full and 5 short papers included in this volume were carefully reviewed and selected from 38 submissions. The papers are organized in topical sections named: process calculi; reversible models; programming languages; quantum computing; quantum programming; circuit theory; and syntheses. .